FAKTOR YANG MEMPERNGARUHI MANAJEMEN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN - Famsila, Ivana; Bangun, Nurainun (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to determine the factors that influence earnings management practice decisions in food and beverage companies listed on the Indonesia Stock Exchange between 2019 and 2021. This study uses probability sampling to collect data from different food and beverage companies. This data involves 40 companies and in this observation the data is processed using Eviews software version 12 and using panel data regression equations. Based on the results of data processing, the independent variable profitability has a significant negative effect on earnings management, although its effect on audit quality is unidirectional (significantly positive). This data also shows that the age of the company has no effect on the dependent variable (earnings management).